José Lezama Lima, extraordinary professor at UCLV: infinite possibility (Islas, 2022)
Introduction: An analysis of the relevant facts found in official documents regarding the relationship between the Cuban intellectual José Lezama Lima and the Universidad Central «Marta Abreu» de Las Villas is proposed. This relationship still presents gaps from the historiographic point of view, which is why this research is necessary. Methods:  Historical-logical methods, analysis and triangulation of documents were applied to unravel the real relationship and interaction between Lezama and the university. The beginning of this relationship was referenced in the official documents of which a deep analysis is made.Results: After the research, it can be affirmed that Lezama's relationship with the university was ephemeral. The analysis of the sources allowed us to establish a logical thread that allows us to know how the contracts, visits, and collaborations in Islas magazine were. It can also be affirmed that the Universidad Central «Marta Abreu» de Las Villas maintained a constant interest in Lezama.Conclusions: Lezama's appointment is the result of the novel perspective of an institution in full formation. His appraisal, and later hiring as extraordinary professor, in spite of not being effective, influenced the editorial and intellectual development of the university.
Keywords: Universidad Central «Marta Abreu» de Las Villas; José Lezama Lima; extraordinary professor